The Use of Engghi-Bhunten Speaking Levels by Madurese Students in Al-Azhar Islamic Boarding School: A Sociolinguistic Study - Heriyanto Nurcahyo; Sukarno; Hairus Salikin (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The speech level of èngghi-bhunten holds significant importance within the broader context of the ML and culture. It refers to a distinct level of speech that reflects cultural values, social norms, and a rich historical layer. This study examines the form, function, factors, and the context of using the ML èngghi-bhunten at the Al-Azhar Islamic Boarding School Situbondo. This research is a type of qualitative research. The method of data collection is in the form of an observation method. The observations carried out included the listening-engagement technique, the free listening-engagement technique, supported by recording and note-taking techniques and supplemented by the interview method. The observation method was employed to observe the use of èngghi-bhunten speech level at Al-Azhar Islamic Boarding School. The researcher recorded social interactions, usage contexts, and the underlying factors behind the use of èngghi-bhunten. Besides, semi-structured interviews were conducted with Madurese students (santri) who possessed knowledge about the usage of èngghi-bhunten. Through these interviews, the researcher gained a deeper understanding of the perceptions, meanings, and contexts surrounding the use of èngghi-bhunten. The collected data were then written in the form of orthographic writing. The analytical method used in this research is contextual analysis, namely the analysis method applied to the data by basing, calculating, and linking the context which is a means of clarifying an intention in the form of a situation related to an event. The results showed that (1) the èngghi-bhunten only used in the dhelem family (Kiai and Nyai); (2) santri always use ML èngghi-bhunten to Kiai and Nyai as a reflection of the Salaf pesantren and as a form of polite manners.